Sistem Pertahanan Kombinasi Untuk Melindungi Kota Pantai Dari Bahaya Tsunami - Edyanto, CB. Herman (Badan Pengkajian dan Penerapan Teknologi, 2015)
Coastal city is a city that is growing rapidly, because the infrastructure is supported by sufficient sea. The potential beauty of the sea make the sea as porches and windows coastal city. This potential drives offer promising investment for the development of economic activities in coastal areas. But what is often forgotten is that the coastal city is inseparable from the problem of disasters, especially tsunamis. Analysis on coastal protection components suggests that coastal vegetation that have adapted to the coastal environment can serve as a coastal defense system in the form of non-structural mitigation. Application of the system of protection as it has financing relatively easy and inexpensive. On the other hand, to further strengthen the protection of tsunami waves and overtopping, structural mitigation remains necessary. The combination of these two systems provide double the power to safeguard the coastal city. This study is a qualitative approach to analyze the non-structural mitigation systems and structural mitigation. A mix of these two systems were able to reduce disaster risk.Kota pantai merupakan kota yang bertumbuh dengan cepat, oleh karena didukung oleh sarana dan prasarana laut yang cukup. Potensi keindahan laut menjadikan laut sebagai serambi dan jendela kota pantai. Potensi ini yang mendorong tawaran investasi yang menjanjikan bagi pembangunan kegiatan ekonomi di kawasan pantai. Namun yang sering terlupakan adalah bahwa kota pantai tidak terlepas dari permasalahan bencana, khususnya tsunami. Analisis terhadap komponen perlindungan pantai memberikan gambaran bahwa vegetasi pantai yang telah beradaptasi dengan lingkungan pantai dapat berfungsi sebagai sistim pertahanan pantai dalam bentuk mitigasi non struktural.Penerapan sistim perlindungan seperti ini memiliki pembiayaan yang relatif mudah dan murah. Disisi lain, untuk lebih memperkuat perlindungan dari gelombang dan limpasan tsunami, mitigasi struktural tetap dibutuhkan. Kombinasi dari kedua sistem memberikan kekuatan ganda bagi upaya perlindungan kota pantai. Pendekatan studi ini bersifat kualitatif dengan menganalisis sistem mitigasi non struktural dan mitigasi structural.Perpaduan antara kedua sistem ini mampu untuk mengurangi risiko bencana.Keywords:Ã‚Â protection, defense, coastal, coastal city, vegetation, tsunami